Numerical Investigations of Flow over Cambered Deflectors at Re = 1 × 105: A Parametric Study - Gang Wang; Zhi Wang; Zhaoqi Jiao; Pihai Gong; Changtao Guan (Biomimetics, 2025)
The cambered deflectors in aquacultural facilities are applied to enhance hydrodynamic efficiencies or enable flow fields to be fully developed. Given the anticipated improvements with the bio-inspired profiles or tandem configurations, the hydrodynamics of cambered deflectors with the above features are investigated at <semantics>Re=1×105</semantics>. The relationship between force coefficients and local flow behaviors for both bionic and non-bionic isolated deflectors, as well as tandem deflectors, is revealed using <semantics>k−ω</semantics> SST simulation. The dependencies of force coefficients on gap (G), stagger (S), and inclination angles (<semantics>θ</semantics>) in tandem deflectors are illustrated using an updated metamodeling workflow with simulated data. It is demonstrated that the variations of force coefficients over angles of attack are related to flow physics in boundary-layer regions. The non-bionic isolated deflector with the <semantics>θ=10∘</semantics> prevails as the decent performances of <semantics>CL</semantics> and <semantics>γ</semantics> globally, which is chosen in the following studies. Regarding tandem deflectors, <semantics>θ</semantics> plays a more vital role in drag coefficients (<semantics>CD</semantics>) and lift coefficients (<semantics>CL</semantics>), while the influence of S is not quite considerable compared to G. Aiming for cost minimizations and lift improvements, an optimized tandem case is obtained and justified with the superiorities in flow fields. This study has provided novel insights into the designs and optimizations of cambered deflectors in aquacultural engineering.